Phylogenetic analysis reveals a high level of speciation in the Paracoccidioides genus - Teixeira, Marcus M.; Theodoro, Raquel C. [UNESP]; Carvalho, Maria J. A. de; Fernandes, Larissa; Paes, Hugo C.; Hahn, Rosane C.; Mendoza, Leonel; Bagagli, Eduardo [UNESP]; San-Blas, Gioconda; Felipe, Maria Sueli S. (Academic Press Inc. Elsevier B.V., 2009)
Paracoccidioidomycosis (PCM) is a systemic disease endemic to most of Latin America, with greatest impact in rural areas. The taxonomic status of one of the best studied Paracoccidioides isolates (Pb01) as A brasiliensis remains unresolved due to its genomic differences from the other three previously described phylogenetic species (S1, PS2 and PS3; Carrero et al., 2008. Fungal Genet. Biol. 45, 605). Using the genealogic concordance method of phylogenetic species recognition (GCPSR) via maximum parsimony and Bayesian analysis, we identified a clade of 17 genotypically similar isolates, including Pb01, which are distinct from the S1/PS2/P3 clade. Consistent with GCPSR, this "Pb01-like" group can be considered a new phylogenetic species, since it is strongly supported by all independent and concatenated genealogies. "Pb01-like" species exhibit great sequence and morphological divergence from the S1/PS2/PS3 species clade, and we estimate that these groups last shared a common ancestor approximately 32 million years ago. In addition, recombination analysis revealed independent events inside both main groups suggesting reproductive isolation. Consequently, we recommend the formal description of the "Pb01-like" cluster as the new species Paracoccidioides lutzii, a tribute to Adolpho Lutz, discoverer of P. brasiliensis in 1908. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Genealogical concordance; Speciation; Phylogenetic species; Molecular phylogeny; Paracoccidioides brasiliensis; Paracoccidioides lutzii